PELATIHAN PEMBUATAN KRUPUK DARI KULIT PISANG PADA KELOMPOK PKK KELURAHAN MALALAYANG DUA, KOTA MANADO - Juliet Makinggung; Rolyke Tulangow; Christien Karambut (Universitas Merdeka Madiun, 2023)
Empowerment is one of the development approaches in improving people's welfare. Economic empowerment through community service activities in the PKK group in Malalayang Dua subdistrict aims to motivate them to be creative in using materials that are no longer useful, especially banana peels to make crackers. Bananas are a fruit that has many benefits. Banana peels also contain sufficient nutritional content and also serotonin which is very vital for balancing mood. Through this community service activity, the Malalayang Dua Village PKK group will receive training on making crackers from banana peels so that unused banana peel waste can be reused and will have selling value if it continues to be developed. The aim of this activity is to provide an understanding of the use of banana peel waste into products that have value through training in making crackers using banana peel as the raw material.